ChemInform Abstract: Catalytic Upgrading of Bio‐Oils by Esterification. Issue 32 (August 2015) - Ciddor, Lachlan; Bennett, James A.; Hunns, James A.; Wilson, Karen; Lee, Adam F.
Abstract Review: 162 refs.